tính tổng 3x-32>-5x+1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(3x-32>-5x+1\)
\(3x>-5x+1+32\)
\(3x>-5x+33\)
\(3x+5x>33\)
\(8x>33\)
=> \(x>\frac{33}{8}\)
Vậy \(x>\frac{33}{8}\)
CÓ 3x - 32 > -5x + 1
<=>3x+ 5x > 1 + 32
<=> 8x > 33
VẬY x > 33/8
\(3x-32>-5x+1\)
\(\Rightarrow8x=33\)
\(\Rightarrow x>\frac{33}{8}\)
\(3x-32>-5x+1\)
\(\Leftrightarrow3x+5x>1+32\)
\(\Leftrightarrow8x>33\)
\(\Leftrightarrow x>\frac{33}{8}\)
\(a,3x-32>-5x+1\)
\(\Leftrightarrow3x+5x>32+1\)
\(\Leftrightarrow8x>33\)
\(\Leftrightarrow x>\frac{33}{8}=4,125\approx4\)
Vậy \(x>4,x\inℤ\)
\(b,15+4x< 2x-145\)
\(\Leftrightarrow4x-2x< -145-15\)
\(\Leftrightarrow2x< -160\)
\(\Leftrightarrow x< \frac{-160}{2}=-80\)
Vậy \(x< -80,x\inℤ\)
\(3x-32>-5x+1\)
\(\Leftrightarrow3x+5x>32+1\)
\(\Leftrightarrow8x>33\)
\(\Leftrightarrow x>\frac{33}{8}\)
L = lim x → − 3 + 2 x 2 + 5 x − 3 x + 3 2 = lim x → − 3 + 2 x − 1 x + 3 x + 3 2 = lim x → − 3 + 2 x − 1 x + 3
Ta có x → − 3 + ⇒ x > − 3 ⇒ x + 3 > 0 ⇒ lim x → − 3 + x + 3 = 0 , và lim x → − 3 + 2 x − 1 = − 7.
Kết luận L = − ∞
Chọn đáp án B.